Yield, seasonality and plant health care of banana ’BRS Conquista’ covered with different coloured polyethylene bags - Martins, Rafaelly Calsavara; Leonel, Sarita; Souza, Jackson Mirellys Azevêdo; Silva, Marcelo de Souza; Ferreira, Rafael Bibiano; Züge, Patrícia Graosque Ulguim; Lorenzetti, Emi Rainildes; Bueno, Regiane Cristina Oliveira de Freitas (Semina: Ciências Agrárias, 2020)
Bananas are the world's most popular fruit. Nonetheless, a great part of the production is lost, mainly for insect and disease incidences. Thus, cover developing banana bunches is a promising physical protection method that will improve the visual quality of the fruits, especially the rapidly growing consumer demand for healthy fruits. In fact, bags serve as protective barrier, allowing the production of free fruit damage; consequently, lowering production costs by cutting crop losses, as well as avoiding chemical materials. There is a wide variety of bag types and colours, but also, there is a scarce literature on their efficiency. This study hence aimed to evaluate the influence of coloured polyethylene bags on yield, seasonality and plant health of the 'BRS Conquista' bananas in subtropical high-altitude growing conditions. Treatments therefore consisted of using white, black, red and blue polyethylene bags, besides control (uncovered). Then, bags were randomly distributed in five blocks, four plants per plot. After bunch harvest, the following evaluation were proceeded: agronomic yield, the interval between bunches cover and harvest, injuries caused by thrips and the incidence of anthracnose. Results indicated that banana bunch coverings did not interfere in bunch yield. Nevertheless, white and black bags reduced the interval between bunch covers and harvest, that is, 114 and 115 days, respectively. Furthermore, white and red bags reduced the damage caused by thrips in fruits; while white, red and blue bags decreased the anthracnose incidence. This study therefore recommends the use of white polyethylene bags to cover banana bunches of the cultivar BRS Conquista, since this bag colour showed highly efficiency in controlling thrips and anthracnose incidence, besides reducing the interval between bunch cover and harvest.